Typical English Teaching Methods Used in Secondary Level - Efendi, Tri Achmad; Arijanto, Alvin Apriliana (Foremost Journal, 2023)
This paper strived to portray the typical English teaching Methods applied by English Secondary teachers. To find the answer, there were twenty-two participants involved in this study, they were from public and private schools in East Java. The study employed qualitative methods with questionnaires, interviews and observations as the instruments. To gain the data, the researchers put all possible teaching activities or techniques taken from the theory of teaching English as a foreign language in the questionnaire. Then, the observations were done to see the actual teaching and learning process in the classroom. At last, the interview was employed to enrich the data. This current study found that mostly teachers under the study claimed to use various teaching activities in the teaching and learning process in their teaching. However, during the observations, teaching activities or techniques mainly were done with the Grammar Translation Method.